CONTROLLING IN ENTERPRISE MANAGEMENT SYSTEM - Besarion C. Meskhi; Vladimir Y. Ivanov (Advanced Engineering Research)
Controlling as a coordinate system of the external and internal environment of the modern enterprise is analyzed. The key functions of controlling, their implementation features are considered.